PERANCANGAN MEDIA KOMUNIKASI VISUAL VIDEO EDUKASI IMPLEMENTASI KURIKULUM MERDEKA DI LOMBOK TIMUR - I Nyoman Miyarta Yasa; Munadiyal Jananti Janap (Berajah Journal, 2026)
This study aims to design an educational video about the implementation of the Merdeka Curriculum in elementary schools (SD) throughout Sakra District, East Lombok. The method used in designing this video is the pipeline method, with qualitative data types. Data were obtained from two sources, namely primary data from elementary school teachers throughout Sakra District, and secondary data including scientific journals, articles, books, and other sources related to the implementation of the Merdeka Curriculum. Data collection was carried out through observation, interviews, and documentation. Data analysis used three main stages: data reduction, data presentation, and drawing conclusions/verification. By presenting a new approach in this educational video, it is hoped that it can help school supervisors in delivering materials and support teachers' understanding regarding the implementation of the Merdeka Curriculum. The resulting educational video is expected to not only be a source of learning for school supervisors and teachers, but also provide long-term benefits for the community and the development of educational video design in the future.